2019
DOI: 10.1007/jhep10(2019)094
|View full text |Cite
|
Sign up to set email alerts
|

On pulsating strings in Schrodinger backgrounds

Abstract: According to AdS/CFT duality semi-classical strings in the Schrödinger spacetime is conjectured to be a holographic dual to dipole CFT. In this paper we consider pulsating strings in five-dimensional Schrödinger space times five-sphere. We have found classical string solutions pulsating entirely in the Schrödinger part of the background. We quantize the theory semi-classically and obtain the wave function of the problem. We have found the corrections to the energy, which by duality are supposed to give anomalo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 74 publications
(105 reference statements)
0
13
0
Order By: Relevance
“…They are in complete agreement with the form of the correlator dictated by the non-relativistic conformal invariance which is a symmetry of the dual theories. Finally, certain pulsating strings solutions in the Schrödinger background were found in [40]. Within the gauge/gravity duality framework, stable configurations of D3-branes play an important role.…”
Section: Introductionmentioning
confidence: 98%
“…They are in complete agreement with the form of the correlator dictated by the non-relativistic conformal invariance which is a symmetry of the dual theories. Finally, certain pulsating strings solutions in the Schrödinger background were found in [40]. Within the gauge/gravity duality framework, stable configurations of D3-branes play an important role.…”
Section: Introductionmentioning
confidence: 98%
“…These studies have been complemented with finite size corrections recently presented in [38]. Pulsating string holography in this background was also studied in [35].…”
Section: Jhep08(2020)090mentioning
confidence: 98%
“…It has been shown that Schrödinger holography matches the anomalous dimensions of certain gauge theory operators with calculation in BMN string limit. The established integrability and results of [30] have motivated further study of the correspondence in non-relativistic cases, see for instance [31][32][33][34][35][36][37]. The BMN string spectrum has been considered in [33] while strings on Schrödinger pp-wave background [36] have been complemented with the study of giant gravitons in the same background [37].…”
Section: Jhep08(2020)090mentioning
confidence: 99%
“…The solution exhibits an intriguing behavior as the deformation parameter varies, which is suggestive of a spontaneous breaking of conformal invariance. Finally, pulsating strings solutions in the Schrödinger background were constructed in [26].…”
Section: Jhep08(2020)091mentioning
confidence: 99%